2017
DOI: 10.1007/s12253-017-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of miR-200c Inhibition on Chemosensitivity (5- FluoroUracil) in Colorectal Cancer

Abstract: 5-Fluorouracil (5-FU) as a chemotherapeutic drug is used to treat colorectal cancer (CRC). However, 5-FU is associated with acquired CRC resistance, which decreases the therapeutic potential of 5-FU. Several studies indicated that miR-200c is also involved in chemotherapeutic drug resistance, but the exact mechanism of miR-200c mediated chemoresistance has not yet been fully understood. In this study, we examined the effect of inhibition of miR-200c on the sensitivity of HCT-116 cells to 5-FU. HCT-116 cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…miR‐200c plays an important role in several biological processes such as EMT, apoptosis, cell invasion, metastasis, and drug resistance (Humphries & Yang, ). Our previous result showed that miR‐200c suppressed the EMT process and increased chemosensitivity of HCT‐116 cells (Heydari et al, ; Karimi Dermani et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…miR‐200c plays an important role in several biological processes such as EMT, apoptosis, cell invasion, metastasis, and drug resistance (Humphries & Yang, ). Our previous result showed that miR‐200c suppressed the EMT process and increased chemosensitivity of HCT‐116 cells (Heydari et al, ; Karimi Dermani et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…It has been revealed that the loss of miR‐200c expression contributes to the acquisition of EMT phenotype and drug resistance. Down‐regulation of miR‐200c by LNA technique has been shown to be associated with EMT phenotype while re‐expression of miR‐200c can result in the reversal of EMT phenotype …”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia tumor microenvironment [37] and enhancement of autophagy procedure [38] both contribute to the chemoresistance of CRC cells. CRCs can also manipulate expression of multiple microRNAs to facilitate their chemoresistance, including suppressing expression of antitumor microRNAs, such as miR-181a/135a/302c [39], miR-874-3p [40], miR-200c [41]; and increasing tumorigenic miRNAs, such as miR-196b-5p [42], miR-315b [43], miR-10b [44].…”
Section: Conclusion and Discussionmentioning
confidence: 99%